Система оцінювання та прогнозування надійності програмного забезпечення - Сенів, М.М.; Федасюк, Д.В.; Парфенюк, Ю.І.; Яковина, В.С.; Чабанюк, Я.М. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
In this paper the architecture and implementation of the software system for software reliability evaluation and prediction based on mathematical reliability model with dynamic index of the software project size have been presented. The system gives the opportunity to computerize the experimental data processing and to evaluate the adequacy of the software testing process.